Heteroheptacene-based acceptors with thieno[3, 2-b]pyrrole yield high-performance polymer solar cells. Issue 7 (27th April 2022) - Luo, Zhenghui; Ma, Ruijie; Yu, Jianwei; Liu, Heng; Liu, Tao; Ni, Fan; Hu, Jiahao; Zou, Yang; Zeng, Anping; Su, Chun-Jen; Jeng, U-Ser; Lu, Xinhui; et al.
Abstract: Rationally utilizing and developing synthetic units is of particular significance for the design of high-performance non-fullerene small-molecule acceptors (SMAs). Here, a thieno[3, 2- b ]pyrrole synthetic unit was employed to develop a set of SMAs (ThPy1, ThPy2, ThPy3 and ThPy4) by changing the number or the position of the pyrrole ring in the central core based on a standard SMA of IT-4Cl, compared to which the four thieno[3, 2- b ]pyrrole-based acceptors exhibit bathochromic absorption and upshifted frontier orbital energy level due to the strong electron-donating ability of pyrrole. As a result, the polymer solar cells (PSCs) of the four thieno[3, 2- b ]pyrrole-based acceptors yield higher open-circuit voltage and lower energy loss relative to those of the IT-4Cl-based device. What is more, the ThPy3-based device achieves a power conversion efficiency (PCE) (15.3%) and an outstanding fill factor (FF) (0.771) that are superior to the IT-4Cl-based device (PCE = 12.6%, FF = 0.758). The ThPy4-based device realizes the lowest energy loss and the smallest optical band gap, and the ternary PSC device based on PM6:BTP-eC9:ThPy4 exhibits a PCE of 18.43% and a FF of 0.802. Overall, this work sheds light on the great potential of thieno[3, 2- b ]pyrrole-based SMAs in realizing low energy loss and high PCE. Abstract : Four heteroheptacene-based acceptors using thieno[3, 2- b ]pyrrole building block were developed for the first time, and all the four acceptors-based devices realized high performance and low energy loss.